ANALISIS PENGEMBANGAN SDM DALAM MENINGKATKAN KETERAMPILAN DIGITAL PELAKU UMKM BINAAN DI PLUT KUMKM CIANJUR - Nisa; Denny Aditya Dwiwarman (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
Abstract The low level of digital skills among MSME players is a challenge in facing the current era of digital transformation. The purpose of this research is to find out about how human resource development in improving the digital skills of assisted MSME players at PLUT KUMKM Cianjur. The research was conducted using a descriptive qualitative approach with data collection techniques conducted through interviews, observation and documentation. Furthermore, data analysis was carried out using SWOT analysis to find out and identify aspects of strengths, weaknesses, opportunities and threats in the process of developing human resources in improving digital skills. The results found in this study indicate that PLUT KUMKM Cianjur must use more optimal and sustainable training and education methods in terms of efforts to improve the digital skills of MSME actors. However, there are still obstacles including the low level of digital literacy of MSME actors, budget constraints and the availability of existing infrastructure. Based on the results in the SWOT analysis, it is found that PLUT KUMKM Cianjur is still lacking in making efforts to develop human resources in improving the digital skills of assisted MSME players, where based on the results of the IFAS and EFAS calculations, it is found that PLUT's position is in quadrant II with an X coordinate value of 1.09 and a Y coordinate of -0.59, which indicates that PLUT has good strengths but is faced with considerable challenges. Therefore, the recommended strategy is to use a diversification strategy, which means that with these severe challenges, it is hoped that the organization will be able to implement various strategies in order to anticipate threats or challenges in efforts to improve the digital skills of assisted MSME actors. Keywords: HR Development, Digital Skills, MSMEs